The Emerging American Garrison State - Esman, Milton J. author. aut Link
VI, 106 p.
Keywords: The constitutional structure of the American federal government is no longer providing responsible and effective governance. To overcome the current paralysis in government, to resume effective management of its crippled economy and of its global empire, a new pattern of government is emerging, one that adheres to the earlier outlines of the garrison state. This volume takes account of the gradual measures that have already been taken to respond to the current paralysis outlines the new pattern of governance that will replace the failing institutions of the constitutional state.